Characterisation of re-entrant circuit (or rotational activity) in vitro using the HL1-6 myocyte cell line. (June 2018) - Houston, Charles; Tzortzis, Konstantinos N.; Roney, Caroline; Saglietto, Andrea; Pitcher, David S.; Cantwell, Chris D.; Chowdhury, Rasheda A.; Ng, Fu Siong; Peters, Nicholas S.; Dupont, Emmanuel
Abstract: Fibrillation is the most common arrhythmia observed in clinical practice. Understanding of the mechanisms underlying its initiation and maintenance remains incomplete. Functional re-entries are potential drivers of the arrhythmia. Two main concepts are still debated, the "leading circle" and the "spiral wave or rotor" theories. The homogeneous subclone of the HL1 atrial-derived cardiomyocyte cell line, HL1-6, spontaneously exhibits re-entry on a microscopic scale due to its slow conduction velocity and the presence of triggers, making it possible to examine re-entry at the cellular level. We therefore investigated the re-entry cores in cell monolayers through the use of fluorescence optical mapping at high spatiotemporal resolution in order to obtain insights into the mechanisms of re-entry. Re-entries in HL1-6 myocytes required at least two triggers and a minimum colony area to initiate (3.5 to 6.4 mm 2 ). After electrical activity was completely stopped and re-started by varying the extracellular K + concentration, re-entries never returned to the same location while 35% of triggers re-appeared at the same position. A conduction delay algorithm also allows visualisation of the core of the re-entries. This work has revealed that the core of re-entries is conduction blocks constituted by lines and/or groups of cells rather than the round area assumed by the other concepts of functional re-entry. This highlights the importance of experimentation at the microscopic level in the study of re-entry mechanisms. Highlights: The cell line HL1-6 makes it possible to examine propagation at the single cell level. A new analysis toolkit permits visualisation of re-entry core in 2D cultures. The number of triggers and re-entries depends on colony size. Re-entry cores are groups of cells connected by thin lines of functional block. The mechanism of re-entry appears comparable with the leading circle concept.